Metaphors for illness in contemporary media. Issue 2 (30th November 2007) - Hanne, M; Hawken, S J
Abstract : Essayist Susan Sontag alerted us more than 20 years ago to the way in which clusters of metaphors attach themselves to our discussion of certain diseases, and the influence these metaphors exert on public attitudes to the diseases themselves and to those who experience them. This study of feature articles on five diseases—avian flu, cancer, diabetes, heart disease, and HIV/AIDS—published recently in the New York Times reveals distinct patterns of metaphor usage around each. While the metaphors used in relation to the diseases Sontag studied—cancer and HIV/AIDS—have become less emotive and more positively informative, the sensationalist connotations of the metaphor clusters that have formed around two diseases that were not on the agenda for wide public debate in her time—avian flu and diabetes—are hardly congruent with the serious intent of the articles in which they appeared. By contrast, discussion of heart disease involved very limited use of metaphor. The article ends with a call for journalists and medical professionals to become more aware of the impact of the metaphors they use and to collaborate in developing sets of metaphors that are factually informative and enhance communication between doctors and their patients.